PELUANG KERJA LULUSAN TEKNOLOGI INFORMASI - Lita Sari Marita (Universitas Bina Sarana Informatika, 2010)
Nowday Bachelor Degree Right in the computer is probably one of the most scholars in Indonesia, Computers and technology are a lot of educational interest to high school graduates, look at so many high schools and universities or colleges also are focusing on information technology field. This also seems causes of development and information technology growing very quickly in Indonesia. Because it is a good idea if we look at any opportunities that arise, what job opportunities are available with the developments in the world of computers and information. To be successful in the field of information technology is necessary recognition of its capability, one of which is to have a certification in the field of information technology. Certification can be held for the recognition of expertise in this field include the certification of Microsoft, Sisco. In addition to having a certification can also standardize the profession. Keywords: Carrier Opportunity, Information Technlogy, Information Technlogy certified